2001
DOI: 10.1002/jmv.2124
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of molluscum contagiosum virus and analysis of the host‐serum antibody response in Spanish HIV‐negative patients

Abstract: Molluscum contagiosum virus (MCV) lesions from Spanish human immunodeficiency virus (HIV)-negative patients were clinically examined and analyzed for virus detection and typing. In a study of 147 patients, 97 (66%) were children under 10 years, of whom 49% had atopic dermatitis. MCV lesions were morphologically indistinguishable among the different age groups, but atopic patients presented larger lesions compared with patients without the disorder. In adults, lesions were observed mainly on the genitals. MCVI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 44 publications
(68 reference statements)
2
23
2
2
Order By: Relevance
“…Because autoinoculation of the virus into the diaper region is the most common source of genital infection in children, MC in the genital area are often seen in children as a part of multiple site involvement [8,15,16]. On the other hand, we found that MC strictly restricted to the genital area were very rare (0.8%).…”
Section: Discussioncontrasting
confidence: 38%
See 3 more Smart Citations
“…Because autoinoculation of the virus into the diaper region is the most common source of genital infection in children, MC in the genital area are often seen in children as a part of multiple site involvement [8,15,16]. On the other hand, we found that MC strictly restricted to the genital area were very rare (0.8%).…”
Section: Discussioncontrasting
confidence: 38%
“…Despite the large number of our patients who were going to the swimming pool (79%, 507/627), we did not find any relation between swimming pool attendance and MC. Twenty-six percent of children with MC (close to the 33% reported by Agromayor et al [15]) were closely related to individuals who themselves were diagnosed with MC, but there was no relation with the number of MC or recurrences. Forty-five percent reported that they had shared a bath with other children (close to the 38% reported by Braue et al [18]) and this was associated with a higher number of MC.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…38 The percentage of patients with MC and AD was reported as high as 49% in a study conducted in Spain. 39 The results of the Spanish study also showed a relation between patients with concurrent AD and large lesions, although these patients had no other distinguishing clinical finding. Overall, the small increase in the percentage of reported MC-infected children with AD as compared with AD in the general population may simply reflect referral bias and the tendency of patients with AD to more readily seek care for skin problems and to be examined regularly by a physician.…”
Section: Discussionmentioning
confidence: 89%